DAMPAK KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SMAIT AL MULTAZAM 2 LINGGAJATI KUNINGAN - Ariyanto; M Syahru Assabana; Suklani; Moh Ahsan (Badan Penerbit STIEPARI Press, 2023)
This study aims to determine the performance of school principals in improving the quality of teaching staff, influencing factors and efforts made by school principals. This study used a qualitative naturalistic approach with a descriptive type which took place at SMAIT Al Multazam 2 Linggajati, Kuningan using data collection techniques, observation, interviews, and documentation. The research results show that: 1). The Head of School Performance in general has shown good and optimal performance and meets the standards and indicators that have been set. This is explained in the